Marriage and Class Struggle Reflected in “Tulip Fever” (2017) Film by Justin Chadwick - Dhikria Istifaroh; Latifah Dwi Ariyani (Metaphor, 2025)
This study aims to analyze: (1) the representation of social class reflected in Tulip Fever (2017), and (2) the marriage of Sophia in Tulip Fever (2017) portrayed as a reflection of class struggle. This study uses a descriptive qualitative method to analyze the film Tulip Fever, directed by Justin Chadwick, as the object of research. The data collection technique includes watching, transcribing, identifying, classifying, and selecting scenes and dialogues related to social class and marriage. The data analysis involves displaying, interpreting, and relating findings to Marxist literary criticism. The theory is used to understand how power, ideology, and class structure influence character interactions. The result of the study show that: (1) social class is clearly represented through characters, spaces, and power dynamics, such as the contrast between the bourgeoisie (Cornelis) and working-class characters (Maria, Willem); and (2) Sophia’s marriage is portrayed not as an emotional choice but as an economic strategy shaped by class oppression. Her failed attempt to rebel reflects the limited autonomy of lower-class women under a capitalist structure.